Definições e rumos na implementação de uma política nacional de assistência ao estudante do ensino superior - Pavan, Flávia Rossi Vacari (2014)
This study aims to establish the theoretical principles and the political and economic interests that guided the implementation of the National Policy for Student Assistance in the structural reform context experienced by the federal universities, mainly from Fernando Henrique Cardoso’s term in the government (1995-2002), which was consolidated in Luiz Inácio Lula da Silva’s governmental term (2003-2010). Coming from a legal perspective of politics, the profile and the interests of the students who are part of the Student Assistance Program of the Federal Univesity of Espirito Santo (UFES) were detailed in order to contribute to the elaboration of future actions which can respond to the needs of this group of students. A literature and a documental review supported by historical and dialectical materialism were made so as to explore the Student Assistance Policy, which is the guiding topic of this research. Through content analysis techniques it was ambitioned to unravel the meaning of the responses given by the students subscribed to the Student Assistance Program of UFES. It became evident that the National Policy of Student Assistance maintains strict relation to the guidance of international organizations that define goals and establish criteria of how to deal with social policies in developing countries. The structural reforms in federal universities, which lay ground to the implementation of the Student Assistance Policy which began in Fernando Henrique Cardoso’s term and stabilized in Lula’s term, paralleled by the Social Assistance Policy, acquired the status of an advance in public policy, however presenting many problems. The theoretical deepening enabled the identification of similarities between the Social Assistance Policy and the Student Assistance Policy, which has been developing a significant role in the undergraduate student’s demands as it enables the maintenance of rights, even if it does not alter the current social structure.